Sharia Cooperatives in Indonesia as an Effort to Create a Sustainable Economy - Sumarlin, Abdul; Muin, Rahmawati; Abdullah, Wahyudin; Jamaluddin, Nurlaeli (Formosa Journal of Multidisciplinary Research, 2024)
This article provides background regarding the development of sharia cooperatives in Indonesia as part of efforts to create a more inclusive and sustainable economy. Sharia cooperatives exist as an alternative that is in accordance with Islamic economic principles, emphasizing economic, moral and ethical aspects of doing business. Even though they are still faced with various challenges, the growth of sharia cooperatives shows a significant impact in empowering communities, especially in areas that were previously less accessible to conventional financial institutions. This article aims to provide a deeper understanding of sharia cooperatives in Indonesia, including history, recent developments, basic principles, roles and challenges faced. The research method used is literature study, by collecting data from various references such as books, articles and journals. The article also reviews regulations that support sharia cooperatives, basic concepts, governance, and the history of their development. By exploring various information related to sharia cooperatives, it is hoped that this article can provide a comprehensive picture of the current condition of sharia cooperatives as well as their potential and challenges in the future.